Prevalence of malnutrition in pediatric pulmonary hypertension cohort and role for registered dietitian involvement - Crowell, Presley R.; Frederick, Mackenzie R.; Fombin, Rozmeen A.; Varghese, Nidhy P.; Ruiz, Fadel E. (Frontiers in Pediatrics, 2023)
Pediatric pulmonary hypertension (PH) is a serious condition with risk for malnutrition due to increased caloric needs and reduced energy intake. This combination of disease and dynamic elements make it challenging to meet expected growth patterns. Pediatric PH patients require close monitoring and individualized nutrition interventions to meet nutrient needs. The prevalence of malnutrition and effective nutrition interventions in pediatric PH has not been studied. Using our electronic medical record (EMR), malnutrition prevalence was assessed by reviewing the active problem list of active PH patients at our center. A chart review compared patients with diagnosed malnutrition in the EMR to those with malnutrition identified by a registered dietitian (RD) using a standardized tool. Chart reviews also assessed outcomes of RD interventions. 195 patients were identified as active PH patients followed during the study period (November 2021 to January 2023). Of these, 5% (10/195) had an ICD-10 code for malnutrition in their chart. Upon further chart review 26% (51/195) had malnutrition identified by a RD using Texas Children’s Malnutrition Tool. The PH RD saw 25/51 (49%) patients during PH clinic visits. At follow up visits, 56% (14/25) patients seen by the PH RD either improved or resolved their malnutrition status by z-score assessment. Malnutrition is present in pediatric PH, although underappreciated and underdiagnosed. Managing malnutrition in pediatric PH requires close monitoring, multidisciplinary involvement, and individualized nutrition recommendations. This is best achieved by RD who is familiar with the unique needs of this population and available to provide consistent assessments and interventions.